Karakter Morfologi dan Produksi Varietas Padi Sawah Lahan Tadah Hujan pada Musim Kemarau - Gymnastiar, Abdullah Hakim; Agustina, Rohmatin (Journal Galung Tropika, 2025)
Rainfed lowland fields represent marginal agroecosystems that are highly vulnerable to drought stress due to their full dependence on rainfall as the primary water source, often resulting in reduced rice productivity. Therefore, adaptive and high-yielding varieties are required to sustain production under these conditions. This study aimed to evaluate the morphological characters and yield performance of five rice varieties, namely MR 20, Kusuma, Inpari 32, IR-64 Jumbo, and Pak Tiwi 2, cultivated in rainfed fields during the dry season. The experiment was arranged in a Randomized Block Design (RBD) with three replications. Observed parameters included vegetative traits, generative traits, biomass, and grain yield per hectare, which were analyzed using ANOVA, LSD test at 5%, and correlation analysis. The results showed that Inpari 32 excelled in vegetative traits and yield components such as panicle length and 1000-grain weight. MR 20 performed best in total grain number, filled grain number, and grain weight per hill, while IR-64 Jumbo produced the longest panicle and the highest yield (7.5 t·ha?¹), comparable to MR 20 (7.3 t·ha?¹). Correlation analysis indicated that grain yield was positively associated with panicle length, total grain number, filled grain number, and root biomass. Overall, MR 20 and IR-64 Jumbo are recommended as adaptive and high-yielding varieties for rainfed lowland fields in the dry season, whereas Inpari 32 is superior in yield components and grain quality.